RESILIENSI PADA IBU HAMIL TRIMESTER III DI PUSKESMAS WILAYAH KAPANEWON SEWON - Suryani, Nadya Ali; Andriyani, Ari; Era Revika; Nur Amellia, Sylvi Wafda (Yayasan Nuraini Ibrahim Mandiri, 2024)
Resilience is the ability of an individual to handle stress or pressure, as well as to manage anxiety and depression. Anxiety has been proven to be a mental disorder that occurs in pregnant women during the third trimester. Psychological changes during the third trimester appear more complex, as the condition is largely due to the growing condition of pregnancy and the lack of preparation for childbirth in the mother, who will be more anxious and show fear, silence, and even tears. Individuals with good resilience will feel capable of achieving their goals even when they are in situations of trauma, tragedy, or events that can cause stress. Resilient individuals will remain calm, think carefully, focus, be able to control themselves, and adapt to the changes they experience, thus not easily feeling anxious and depressed. This study aims to understand the resilience of pregnant women at the Sewon Kapanewon Health Center. This study is quantitative with a descriptive quantitative method. The sampling technique used is Aksidental Sampling with a sample size of 84 individuals. The instrument used is the Connor-Davidson Resilience Scale 25 (CD-RISC 25). Based on the results of the CD-RISC 25 questionnaire, the resilience level of pregnant women in the third trimester at Sewon Health Center I and II shows that 67 pregnant women (79.5%) have moderate resilience, 17 pregnant women (20.5%) have high resilience, and no low resilience (0%). The results of this study serve as a source of data and a reference for developing more effective programs or interventions by healthcare professionals in addressing mental health issues.